2002
DOI: 10.1111/1529-1006.00007
|View full text |Cite
|
Sign up to set email alerts
|

“Brain-Specific” Nutrients: A Memory Cure?

Abstract: We review the experimental evaluations of several widely marketed nonprescription compounds claimed to be memory enhancers and treatments for age-related memory decline. We generally limit our review to double-blind placebo-controlled studies. The compounds examined are phos-phatidylserine (PS), phosphatidylcholine (PC), citicoline, piracetam, vinpocetine, acetyl-L-carnitine (ALC), and antiox-idants (particularly vitamin E). In animals, PS has been shown to attenuate many neuronal effects of aging, and to rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 94 publications
0
25
0
Order By: Relevance
“…The main mechanism of action of ALC is the improvement of mitochondrial respiration which allows the neuron to produce ATP necessary to maintain the normal membrane potential [251]. However, ALC has been shown to be neuroprotective through a variety of other effects such as the increase in PKC activity [251].…”
Section: Natural Antioxidants Vitagenes and Neurodegenerative Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…The main mechanism of action of ALC is the improvement of mitochondrial respiration which allows the neuron to produce ATP necessary to maintain the normal membrane potential [251]. However, ALC has been shown to be neuroprotective through a variety of other effects such as the increase in PKC activity [251].…”
Section: Natural Antioxidants Vitagenes and Neurodegenerative Disordersmentioning
confidence: 99%
“…The main mechanism of action of ALC is the improvement of mitochondrial respiration which allows the neuron to produce ATP necessary to maintain the normal membrane potential [251]. However, ALC has been shown to be neuroprotective through a variety of other effects such as the increase in PKC activity [251]. Interestingly ALC counteracted the loss of NMDA receptors in neuronal membrane and increased the production of neurotrophins, two effects strictly related to synaptic plasticity [251].…”
Section: Natural Antioxidants Vitagenes and Neurodegenerative Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroprotective dietary components have an essential role in facilitating healthy ageing of the brain (Devi and Kiran 2004;Joseph et al 2005). Dietary antioxidants from fruits and vegetables have preventative effects on oxidative stress (Bastianetto and Quirion 2002;Esposito et al 2002;Galli et al 2002;McDaniel et al 2003;Schmitt-Schillig et al 2005;Youdim et al 2002). Green tea catechin (GT-catechin) is a mixture of plant polyphenols that have potent antioxidative and radical-scavenging activities (Kashima 1999;Kimura et al 2002;Levites et al 2001;Nanjo et al 1999;Skrzydlewska et al 2002;Suzuki et al 2004;Terao 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that some psychological dimensions, such as cognitive performances, mood and the perceived stress may change or decrease in ageing, particularly from the age of 60 years (McDaniel et al 2003;Marcellini et al 2006). It has been suggested that mood disorders and depressive status may be accompanied by lowered serum zinc concentrations (Maes et al 1999), which lead to frailty, general disability and increased incidence of agerelated degenerative diseases .…”
Section: Introductionmentioning
confidence: 99%